2009
DOI: 10.1194/jlr.m900034-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoAI processing by procollagen C-proteinase enhancer-2 and bone morphogenetic protein-1

Abstract: Given the increased prevalence of cardiovascular disease in the world, the search for genetic variations controlling the levels of risk factors associated with the development of the disease continues. Multiple genetic association studies suggest the involvement of procollagen C-proteinase enhancer-2 (PCPE2) in modulating HDL-C levels. Therefore biochemical and mechanistic studies were undertaken to determine whether there might be a basis for a role of PCPE2 in HDL biogenesis. Our studies indicate that PCPE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
1
46
1
1
Order By: Relevance
“…However, the extent of collagen fibril abnormalities in tissues of PCPE1-null mice (46) suggests possible additional roles for PCPEs. Suggestive but inconclusive genetic studies have implicated PCPE2 in modulating serum levels of HDL, whereas biochemical studies have shown PCPE2 to be associated with serum HDL and to be capable of binding both pro-ApoA1 and BMP1 and perhaps enhancing proApoA1 processing by BMP1 in vitro (88). In vivo roles for PCPE2 in modulating HDL levels and pro-ApoA1 processing are supported by recent findings of decreased pro-ApoA1 processing and changes to HDL levels and properties in PCPE2-null mice (89).…”
Section: Pcp Enhancersmentioning
confidence: 49%
“…However, the extent of collagen fibril abnormalities in tissues of PCPE1-null mice (46) suggests possible additional roles for PCPEs. Suggestive but inconclusive genetic studies have implicated PCPE2 in modulating serum levels of HDL, whereas biochemical studies have shown PCPE2 to be associated with serum HDL and to be capable of binding both pro-ApoA1 and BMP1 and perhaps enhancing proApoA1 processing by BMP1 in vitro (88). In vivo roles for PCPE2 in modulating HDL levels and pro-ApoA1 processing are supported by recent findings of decreased pro-ApoA1 processing and changes to HDL levels and properties in PCPE2-null mice (89).…”
Section: Pcp Enhancersmentioning
confidence: 49%
“…The CUB domains facilitate protein-protein interactions, in this case BMP-1 and PCPE1 to allow for the productive cleavage of the C-terminal prosequence from procollagen. The cleavage of pro-apoA-I is by a very similar process involving BMP-1 ( 5 ) and PCPE2 forming a complex with the proapoprotein, again via the CUB domains of the fi rst two components ( 6 ). Binding studies suggest that the order of addition of these components to the complex may favor the association of pro-apoA-I with BMP-1 followed by the addition of PCPE2.…”
Section: Pro-apoa-i Maturation (Cleavage)mentioning
confidence: 95%
“…Procollagen C-endopeptidase enhancer (pcpe) can regulate the level of high-density lipoprotein (HDL) particles in vivo (Zhu et al 2009). HDL particles have the function of anti-inflammatory, anti-aggregative and antioxidant properties Stein 1999, Fredenrich andBayer 2003).…”
Section: Discussionmentioning
confidence: 99%